Eco-friendly reduced graphene oxide for the determination of mycophenolate mofetil in pharmaceutical formulations - Prashanth S. Narayan; Nagappa L. Teradal; Seetharamappa Jaldappagari; Ashis K. Satpati (Elsevier, 2018)
Graphene oxide (GO) was synthesized and characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM), X-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA). GO was then electrochemically reduced and used for electrochemical study of mycophenolate mofetil (MMF). The electrochemically reduced graphene oxide (ERGO) film on glassy carbon electrode (GCE) showed enhanced peak current for electrooxidation of MMF. MMF exhibited two irreversible oxidation peaks at 0.84 V (peak a1) and 1.1 V (peak a2). Effects of accumulation time, pH and scan rate were studied and various electrochemical parameters were calculated. A differential pulse voltammetric method was developed for the determination of MMF in bulk samples and pharmaceutical formulations. Linear relationship was observed between the peak current and concentration of MMF in the range of 40 nM-15 μM with a limit of detection of 11.3 nM. The proposed method is simple, sensitive and inexpensive and, hence, could be readily adopted in clinical and quality control laboratories. Keywords: Mycophenolate mofetil, Electroreduced graphene oxide, Electrochemical sensor, Analytical application